THE IMPACT OF PROGRAM FOR INCREASE PRODUCTION AND HORTICULTURAL ADDED VALUE TO THE COMPETITIVENESS OF SHALLOT FARMING IN SERANG REGENCY - Dian Anggraeini; Aliudin Aliudin; Jejen Aripin (Syarif Hidayatullah State Islamic University Jakarta, 2022)
Shallots are a strategic commodity in Indonesia. The potential and benefits that shallot have caused the demand for shallots to increase along with the increasing population. Serang Regency has not been able to meet its high demand. The shortage of local shallot production is met by bringing in shallots from outside Serang Regency. One of the government's efforts to increase shallot production is the implementation of Program Pof the increase in Produces and Value-Added Horticulture, the purpose of the program is to increase shallot production and farmers' income. How the government intervention is assessed, this research aims to analyze the impact of the Horticultural Production and Value-Added Increase Program on the competitiveness of shallot farming in Serang Regency. This research is descriptive-analytic. The sampling method used is purposive. Data collection was carried out through interviews, observations, and documentation. Data analysis using a policy analysis matrix (PAM). The results showed that the program generates private and social benefits of positive value so that the development of the shallot area can continue to run which is beneficial to farmers and the community, the program is also able to increase farmers' income by 57.17 percent. The value of the government protection indicator is positive, which means that the government has effectively protected shallot farming. In addition, result research shows that shallot farming under Program P leveling Produces and Value-Added Horticulture has competitiveness through competitive and comparative advantages so the development of shallot areas in Serang Regency deserves to be prioritized in its development. recommended policy recommendations to increase farmers' income and competitiveness through the efficient use of production inputs that refer to technological advice and increase the capacity of human resources and farmer institutions